Comparing the Agency Costs of Family and Non–Family Firms: Conceptual Issues and Exploratory Evidence - Chrisman, James J.; Chua, Jess H.; Litz, Reginald A. (Entrepreneurship Theory and Practice, 2004)
Family involvement in a business has the potential to both increase and decrease financial performance due to agency costs. In this article we discuss the different nature of agency costs in family firms and specify the combination of conditions necessary to determine the relative levels of agency costs in family and non–family firms through the impacts of agency cost control mechanisms on performance. We also present exploratory results based on a study of 1,141 small privately held U.S. family and non–family firms that suggest the overall agency problem in family firms could be less serious than that in non–family firms.